PENGEMBANGAN ENSIKLOPEDIA BERBASIS POTENSI LOKAL DAERAH PERBATASAN DI KALIMANTAN UTARA PADA MATERI SUMBER DAYA ALAM - Fadhlan Muchlas Abrori; Alfian Mucti; Listiani Listiani (Universitas Borneo Tarakan, 2019)
Abstract: Leaning in the classroom now need effective and efficient process. Effective and efficient learning process need joyfull learningmedias. The media that have that charaterictics is encyclopedia.Developing an encyclopedia need to insert region’s local potiencies, soit can have uniqueness characteristics. The goals of this reseach anddevelopment are to understand the quality of encyclopedia based onlocal potencies in border region in North Kalimantan at naturalresources content. Its quality are reviewed from experts suitabilityaspect and field test. Reseach approach used research and development.Developing model that was used in this research and development wasmodification of 4D model. Based on the research, assessment resultfrom material expert obtained 87,8% (valid). Assessment result frommedia expert obtained 94% (valid). Asessment result form linguisticexpert obtained 92% (valid). Based on teacher and students assessment,the encyclopedia from teacher was obtained 87.4 and its percentageform students was 83.5%.